2018
DOI: 10.1051/0004-6361/201731739
|View full text |Cite
|
Sign up to set email alerts
|

Solid H2 in the interstellar medium

Abstract: Context. Condensation of H 2 in the interstellar medium (ISM) has long been seen as a possibility, either by deposition on dust grains or thanks to a phase transition combined with self-gravity. H 2 condensation might explain the observed low efficiency of star formation and might help to hide baryons in spiral galaxies. Aims. Our aim is to quantify the solid fraction of H 2 in the ISM due to a phase transition including self-gravity for different densities and temperatures in order to use the results in more … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Moreover, Seligman & Laughlin (2020) confirmed that H 2 O could not be the dominant accelerant and ruled-out CO 2 . H 2 ice was discussed as a possible constituent of 'Oumuamua by Füglistaler & Pfenniger (2018) and reconciled with the energy balance of the non-gravitational acceleration by Seligman & Laughlin (2020). Molecular nitrogen ice was demonstrated to be consistent with the non-Keplerian trajectory by .…”
mentioning
confidence: 88%
“…Moreover, Seligman & Laughlin (2020) confirmed that H 2 O could not be the dominant accelerant and ruled-out CO 2 . H 2 ice was discussed as a possible constituent of 'Oumuamua by Füglistaler & Pfenniger (2018) and reconciled with the energy balance of the non-gravitational acceleration by Seligman & Laughlin (2020). Molecular nitrogen ice was demonstrated to be consistent with the non-Keplerian trajectory by .…”
mentioning
confidence: 88%
“…As shown previously, water ice radiolysis produces large quantities of H 2 in the first meters of the subsurface. At cometary nucleus temperature, H 2 sublimates rapidly (Greenberg & de Jong 1969;Füglistaler & Pfenniger 2018). Due to the high porosity of the nucleus, it is thus likely that a significant part outgasses from the comet.…”
Section: Impact Of Gcr On Chemical Compositionmentioning
confidence: 99%
“…Moreover, comets are expected to persist indefinitely in the galactic environment, and so it is surprising that the first-detected ISO had kinematics associated with an extremely young age. Füglistaler & Pfenniger (2018) raised the possibility that 'Oumuamua could be composed of H 2 ice. This hypothesis was further developed by Seligman & Laughlin (2020) who showed that solid hydrogen can plausibly explain 'Oumuamua's unusual properties.…”
Section: Introductionmentioning
confidence: 99%